Bridge Individuals in Multinational Organisations. (1st July 2016) - Sekiguchi, Tomoki
Abstract : In multinational organisations, individuals who mediate or bridge between different national and cultural groups, such as headquarters (HQ) and foreign subsidiaries, play a critical role and are known as 'bridge individuals'. This perspective article reviews the recent literature on bridge individuals and offers future research directions in which organisational psychology can contribute to the deeper understanding of the individuals in this role. I propose the interdisciplinary approach, in which knowledge of organisational psychology and other academic fields, such as cognitive linguistics, cross-cultural communication, and social network theory, are integrated when studying bridge individuals.